The role of atorvastatin on the restenosis process post-PTA in a diabetic rabbit model. Issue 1 (December 2016) - Zhou, Xiaojun; Mou, Yaru; Shen, Xue; Yang, Tianshu; Liu, Ju; Liu, Fupeng; Dong, Jianjun; Liao, Lin
Abstract Background Restenosis remains to be a major limitation of percutaneous transluminal angioplasty (PTA) for diabetic patients with peripheral vascular disease (PVD). Despite of stations routine implements to prevent such progress, its exact effect is unclear. Methods and results In our study, balloon was successfully implanted in the iliac artery of atherosclerotic rabbit. Patency of the narrowed artery was interrogated using ultrasound. Atorvastatin or vehicle was administered orally to rabbits from day 0 to day 28 after double-injury surgery. On day 7, day 14, and day 28, restenotic arteries were harvested and processed for histopathlogical analysis. Our data show that, after double-injury surgery, the intima was composed mostly by SMCs at all time course in rabbits undergoing surgery process. Significant increases in stenosis rates were noted from day 7 to day 14 (from 21 ± 5.85 % to 60.93 ± 12.46 %). On day 28 after double-injury surgery, severe restenosis was observed and daily administration of atorvastatin cannot prevent restenosis' formation (88.69 ± 3.71 % vs. 90.02 ± 3.11 %, P  > 0.05). The PCNA index and SMCs proliferation were correlated with the scores of the vascular pathology. Conclusions Our results indicate that double-injury model can mimic clinical restenosis, based on this model, atorvastatin showed no therapeutic effect on restenosis process in diabetic rabbits after PTA.